Institutional options for the conservation of biodiversity : evidence from the Czech Republic - Tomás Ratinger; Veronika Krumalová; Jaroslav Prazan (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2004)
The paper focuses on changes in property rights and policies regarding interactions between agriculture and nature in the Czech Republic. In the first part the recent situation is reviewed. The institutional and organisational features and their development during the transition and recent years are illustrated by the case study on the White Carpathian protected landscape area. The key issue in conservation in the White Carpathians (as in the number of other marginal areas) is to maintain grassland management at large scale. While environmental policy lacks measures for maintaining grassland management, respective incentives were launched in the frame of agricultural policy, although they do not sufficiently consider environmental concerns. There are two other problem areas hampering efficient organisation of conservation: uncompleted land reform and little involvement of local population in determining conservation priorities. In the second part, the paper examines three policy options for enhancing sustainability of landscape and biodiversity on farmland. The proposed policy options each reflect the identified problems in the White Carpathian case study.
Keywords: 330; Biodiversität; Landwirtschaft; Agrarverfassung; Tschechische Republik; Karpaten